2008
DOI: 10.1038/sj.eye.6703072
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma and mortality in the Beijing Eye Study

Abstract: Purpose To assess the relationship between glaucoma and mortality in a population-based setting. Methods At baseline in 2001, the Beijing Eye Study examined 4356 subjects for glaucoma with a detected glaucoma frequency of 135/ 4356 or 3.1%. Mean age was 55.9 ± 10.4 years (40-101 years). In 2006, all study participants were reinvited for a follow-up examination. Results Out of the 4356 subjects, 3208 (73.6%) subjects returned for follow-up examination, while 124 (2.8%) subjects were dead, and 1024 (23.5%) subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
(26 reference statements)
0
16
1
2
Order By: Relevance
“…Unlike Beijing Eye Study, we did not find an association between PAC and PACG with mortality 17. This could be attributed to factors specific to the population or study design or the confounders adjusted in analysis as described above.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Unlike Beijing Eye Study, we did not find an association between PAC and PACG with mortality 17. This could be attributed to factors specific to the population or study design or the confounders adjusted in analysis as described above.…”
Section: Discussioncontrasting
confidence: 77%
“…Most of these studies were undertaken in Caucasian populations and most focused on POAG—only one study investigated a black population 16. In the only study from Asia, there was a strong association between mortality and PACG but not with POAG 17. Reports on the association of mortality with raised intraocular pressure (IOP) and pseudoexfoliation (PXF) are also inconsistent with some showing an association10 16 whereas others have not 12 18–20.…”
Section: Introductionmentioning
confidence: 99%
“…High myopia defined as a myopic refractive error > − 8 D was present in 1.5% (95% CI 1.1–1.9) of the subjects. It was significantly (p < 0.001) associated with lower BCVA, larger optic disc size, larger size of beta zone and alpha zone of peripapillary atrophy, and a lower macular drusen count (p = 0.02) (Xu et al. 2007a).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 4439 subjects who participated in the survey in 2001, 3251 (73.2%) returned for follow-up examination; 143 (3.2%) subjects had died and 1045 (23.5%) subjects did not agree to be re-examined or had moved away (Xu et al 2008g). The mortality rate was significantly (p < 0.001; OR = 4.72, 95% CI 2.67, 8.33) higher in the glaucoma subjects (11.1 ± 2.7% [95% CI 5.8, 16.4]) than in the participants without glaucoma (2.6 ± 0.2% [95% CI 2.2, 3.0]).…”
Section: Glaucoma and Mortalitymentioning
confidence: 99%
“…The associations between body height and ocular parameters may have an additional clinical meaning. A recent study suggested that subjects with angle-closure glaucoma have a higher mortality than subjects with open-angle glaucoma or non-glaucomatous subjects [20]. The reason for the higher mortality of subjects with angle-closure glaucoma may have been that these subjects had a smaller body stature due to the association between anterior chamber depth and body height.…”
Section: Discussionmentioning
confidence: 97%